Structural characterisation of the bromouracil.guanine base pair mismatch in a Z-DNA fragment. - Brown, T; Kneale, G; Hunter, W; Kennard, O (1986)
The deoxyoligonucleotide d(BrU-G-C-G-C-G) was crystallised at pH 8.2 and its structure analysed by X-ray diffraction. The unit cell, of dimensions a = 17.94, b = 30.85, c = 49.94A contains four DNA duplexes in space group P2(1)2(1)2(1). The duplexes are in the Z conformation, with four Watson-Crick G.C base pairs and two BrU.G base pairs. The structure was refined to an R factor of 0.16 at a resolution of 2.2A with 64 solvent molecules located. The BrU.G base pair mismatch is of the wobble type, with both bases in the major tautomer form and hydrogen bonds linking 0-2 of BrU with N-1 of G and N3 of BrU with 0-6 of G. There is no indication of the presence of ionised base pairs, in spite of the high pH of crystallisation. The results are discussed in terms of the mutagenic properties of 5- bromouracil.